Sorotan Kajian Lepas: Teori dan Amalan dalam Penyelidikan Islam - Abdul Rahim, Rahimin Affandi; Awang, Idris (Jurnal Fiqh, 2006)
The article attempts to discuss the significance and functions of review literature in research especially as guide to young researchers. Basically, the review enables a researcher to have an up-to-date understanding of the research problem and to avoid him from attempting unnecessarily to understand what has been fully understood. The review will help the researcher to have relevant information of the context of the problem because a problem does not exist by itself, there must be certain relationship with other problems. This is essential when trying to find solution to the problem. The review also exposes the researcher to the related theories that will enable him to plan the research appropriately.